Determinants of Performance of Conventional and Islamic Banks in GCC - ALABBADI, ALAEDDIN (2017)
The aim of this research is to evaluate the impact of internal and external variables on the performance of both Islamic banks and conventional banks in the GCC. The Internal variables include capital adequacy, asset quality, management, earnings, liquidity and sensitivity of risk while the external variables are the economic growth and inflation. Return on equity and Return on asset were used in the STATA programming to identify the variable with the greatest effect or least effect on the performance of banks in GCC. Specifically, five conventional banks and five Islamic banks from 2012 to 2015 were used in the research.